Causative constructions and aspectual meanings: a case study from semitic derivational morphology - Tsarfaty, Reut (Proceedings of the Amsterdam Colloquium, 2005)
This work aims at identifying aspectual properties of events denoted by morphological causatives in Modern Hebrew (MH). The main purpose of this investigation is to establish a clear connection between causative constructions and aspectual meanings, two notions that are not so easily correlated. A secondary goal is to argue for the systematic aspectual contribution of Semitic derivational morphology. Our theory is inspired by Smith’s causal chain and builds on a thematic account of Semitic derivational morphology. Combining a formal and empirical investigation we argue that the MH causative template Hiph’il shifts the viewpoint of an event onto its initiation and development phases, making it more appropriate for imperfective use.